A short pyrene-fused pyrazaacene with red to near-infrared photoluminescence1. Issue 38 (11th May 2015) - García, Raúl; Melle-Franco, Manuel; Mateo-Alonso, Aurelio
<x xml:space="preserve">Abstract</x> A pyrene-fused pyrazaacene with only four linearly-fused aromatic rings is reported, which remarkably shows emission at red to NIR wavelengths (λem = 687 nm).